2021
DOI: 10.24059/olj.v25i1.2474
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Academic Performance and Student Satisfaction during the Remote Transition of a Nursing Obstetrics Course to Online Instruction

Abstract: This study explores the effect of rapidly transitioning an in-person pre-licensure nursing specialty course to remote instruction during the COVID-19 pandemic. The redesign included the following learning technologies: live and recorded whiteboard lectures with Socratic-style questioning, electronic audience response systems, remote simulations, and virtual unfolding case studies to replace didactic and clinical learning experiences. Quantitative results indicate that learning quality was sustained, with no si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
1
7
0
7
Order By: Relevance
“…Survey results revealed that students had generally positive perceptions about online learning during the pandemic and the majority of them wanted to continue with some online learning post pandemic. Overall, our findings supported several other studies in dental [ 18 , 20 ], medical [ 43 , 44 ], and nursing [ 45 ] education that have also reported students’ positive attitudes towards online learning during the pandemic. In their written comments in the survey, students cited enhanced flexibility as one of the greatest benefits of online learning.…”
Section: Discussionsupporting
confidence: 91%
“…Survey results revealed that students had generally positive perceptions about online learning during the pandemic and the majority of them wanted to continue with some online learning post pandemic. Overall, our findings supported several other studies in dental [ 18 , 20 ], medical [ 43 , 44 ], and nursing [ 45 ] education that have also reported students’ positive attitudes towards online learning during the pandemic. In their written comments in the survey, students cited enhanced flexibility as one of the greatest benefits of online learning.…”
Section: Discussionsupporting
confidence: 91%
“…Focusing on promoting student inclusion with belongingness and clinical reasoning ( Hunter & Arthur, 2016 ) combined with case studies or virtual simulations as a teaching modality can accomplish student goals for clinical. Riley et al (2021) discuss virtually delivering an obstetrics course; changes include unfolding case studies with student participation and result in unchanged student scores and satisfaction in comparison to previous sessions. Editorials discuss clinical changes in response to COVID-19 and recommend a review of outcomes compared to traditional programming ( Jackson et al, 2020 ; Morin, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another group of studies, researchers shared their experience or thoughts about existing OL programs (Long, 2020), delivering courses online (García-Alberti et al, 2021), redesigning course content for OL (Reck, 2020;Riley et al, 2021;Streveler & Smith, 2020), improving online delivery of specific courses (Giles & Willerth, 2021;Zapanta et al, 2021), using new approaches for effective online teaching (Alqahtani & Rajkhan, 2020), enhancing student selfstudy (Balakrishnan & Long, 2020), enhancing student engagement (Mosquera Feijóo et al, 2021;Prince et al, 2020), applying new methods for student assessment (Barra et al, 2020;Teo & Pueh, 2020), and enhancing student motivation (Leung & Chu, 2020;Miller, 2020).…”
Section: Transitioning To Ol During Covid-19mentioning
confidence: 99%